ANALYSIS OF THE NUMBER OF DEATHS DUE TO MALIGNANT NEOPLASMS OF THE LIP, ORAL CAVITY AND PHARYNX IN THE STATE OF PERNAMBUCO - HISTORICAL SERIES FROM 1996 TO 2019 - Thaís Duarte Brasileiro, Camilla; Letícia Passos Santos, Maria; Carvalho Bruno dos Santos, Matheus; da Mota Vasconcelos Brasil, Catarina; Paulo Mello Lócio, João (Health and Society, 2021)
According to the World Health Organization (WHO), the second cause of morbidity and mortality in Brazil is cancer. Malignant neoplasm of the head and neck is considered one of the main tumors in Brazil and in the world, with high mortality rates. This is due to the diagnosis, which is made late, often when the disease has advanced clinical stages, reaching metastasis. This work is a descriptive study of secondary data carried out through a survey by the Department of Informatics of the Brazilian Unified Health System. After obtaining the data, they were tabulated. A literature review was also carried out to support the research, using the Google Academic, Scielo and Pubmed platforms. The analysis was performed using mortality data from malignant neoplasms of the lip, oral cavity and pharynx in Pernambuco from 1996 to 2019 and, according to the survey, 6,121 deaths were registered. The data showed a higher mortality rate in males; patients between 55 and 64 years old; in addition to brown people. The highest number of deaths in individuals with less education was also observed. Although studies on the prevention and cure of cancer are currently intermittent, the data analyzed show that the rates of appearance of new cases have grown in recent years and tend to increase in the next due to daily life habits. Thus, it is important to invest in research aimed at inhibiting the appearance of new neoplasms.